1) Développer, réduire et ordonner les expressions suivantes:
b= (3x-4)²+ (2x-3) (3x+4)
c= (5x+3)²- (2x-3)²
2) Factoriser les expressions suivantes:
d= 3(x+2)² (x-1)-(x+2) (x-1)²

2
b= (9xau carré - 24x + 16) + (6 xaucarré + 8x -9x -12)
b= 9xau carré - 24x + 16 +6 xaucarré + 8x -9x -12
b=15xau carré -25x +4
merci! pour le b

Réponses

2014-10-04T10:12:55+02:00
c= (5x+3)²- (2x-3)²
c= (25x² + 30x + 9) - (4x² - 12x + 9) 
c= 25 x² + 30x + 9 - 4x² +12x -9
c= 21x² + 42x 
2014-10-04T12:06:31+02:00
C=25xaucarre+30x+9-4xaucarre+12x-9
C=21xaucarre+42x
et voila